Interest of Students With Hearing Obstacles to Continue Education to College - Fajarwati, Nur Tyara; Hernawati, Tati; Gunawan, Dudi (Universitas Pendidikan Indonesia (UPI), 2021)
To gain higher education is the right of all people without exception, including children with hearing impairment. Interest factor becomes very important to fulfill their hope to continue education of higher education. Therefore, this research aimed to know (1) students’ with hearing impairment interest to continue education of higher education, (2) Factors that influence students ’ with hearing impairment interest to continue education of higher education. This research used qualitative approach with descriptive method. Data collecting technique did by interview and documentary study. This research result showed that from four subjects researched there are two subjects of SMALB SLB BC YP Al-Azhar Leuwimunding that interest to continue education of higher education, this case can be seen from the happiness and interested to study subjects such as cosmetology and the art of dance that based on the subject’s dreams. Furthermore, the subject’s interest to continue of higher education caused by internal factor such as motivation inside subject